On the past, present, and future of the Diebold-Yilmaz approach to dynamic network connectedness - Francis X. Diebold; Kamil Yılmaz (Koç University-TÜSIAD Economic Research Forum (ERF), 2022)
We offer retrospective and prospective assessments of the Diebold-Yilmaz connectedness research program, combined with personal recollections of its development. Its centerpiece in many respects is Diebold and Yilmaz (2014), around which our discussion is organized.
Keywords: C1; C3; G1; 330; Contagion; Spillovers; Financial markets; Vector autoregressions; Variance decompositions